The Influence of Social Capital, Intellectual Capital, and Financial Capital on the Growth of Young Entrepreneurs in West Java - Coryanata, Isma; Hakim, Latifa Dinar Rahmani (West Science Business and Management, 2025)
This study investigates the influence of social capital, intellectual capital, and financial capital on the growth of young entrepreneurs in West Java. Young entrepreneurs play a vital role in driving regional economic development; however, their business growth is often constrained by limited resources, capabilities, and access to financing. This research adopts a quantitative approach using data collected from 150 young entrepreneurs in West Java through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using multiple linear regression with the aid of SPSS version 25. The results reveal that social capital has a positive and significant effect on the growth of young entrepreneurs, indicating that networks, trust, and collaborative relationships contribute to improved business performance. Intellectual capital shows the strongest positive influence on entrepreneurial growth, emphasizing the importance of knowledge, skills, creativity, and innovation capability in sustaining and expanding businesses. Financial capital also has a positive and significant effect on growth, although its influence is relatively smaller compared to social and intellectual capital. Simultaneously, social capital, intellectual capital, and financial capital explain 46.8% of the variation in entrepreneurial growth. These findings highlight that the growth of young entrepreneurs in West Java is shaped by an integrated combination of relational, knowledge-based, and financial resources. The study provides practical implications for policymakers and entrepreneurship support institutions to design comprehensive programs that strengthen networks, enhance entrepreneurial competencies, and improve access to finance.